Integrated Care Model by the Village Health Volunteers to Prevent and Slow down Progression of Chronic Kidney Disease in a Rural Community, Thailand - Ampornpan Theeranut; Nonglak Methakanjanasak; Sunee Lertsinudom; Pattama Surit; Nichanun Panyaek; Saisamon Leeladapattarakul; Peangtikumporn Nilpetch; Pattapong Kessomboon; Chalongchai Chalermwat; Watcharapong Rintara; Wudipong Khongtong; Pawich Paktipat; et al. (SAGE Publishing, 2024)
Introduction: Chronic kidney disease (CKD) is a major health problem in Thailand and health behaviors are central to its risk and progression. Because of the shortage of healthcare personnel, village health volunteers (VHVs) have been collaborating in the primary health care system. However, the contribution of VHVs to CKD reduction has not been evaluated yet. This study aimed to evaluate the efficacy of the VHV-integrated model in preventing and slowing down CKD and its risk factors. Methods: The population-based cohort study was conducted in a rural community of Thailand between 2017 and 2019. Baseline clinical and behavioral characteristics including CKD, diabetes, hypertension, and other high-risk factors of the participants were collected. The integrated care model was initiated by the multidisciplinary care team that facilitated, empowered, and trained VHVs targeting risk factors of CKD, health literacy, and health promotion. Then the participants were educated and trained for lifestyle modification and were monitored continuously for 18 months by VHVs. Changes in the CKD risk factors, and kidney functions before and after the application of integrated care model were compared. Results: A total of 831 subjects participated in the study with an average age of 57.5 years, and 69.5% were female. Among them, 222 participants (26.7%) were diagnosed as having CKD, the vast majority (95%) of which were in the early stages (G1-G3 and A1-A2). CKD risk factors such as high salt intake, smoking, alcohol consumption, self-NSAID (non-steroidal anti-inflammatory drugs) use were significantly decreased after application of the care model. Also, hemoglobin A 1c was significantly reduced in diabetic patients, and blood pressure was controlled better than before in the hypertensive patients. Most importantly, a decline of estimated glomerular filtration rate of the CKD group was improved and lower than the non-CKD group. Conclusion: The integrated care model through VHV significantly attenuated the risk factors associated with CKD in the general and high-risk population and effectively slowed down the progression of CKD.